A voraz-cidade: procedimentos de construção do midiático na obra de Rubem Fonseca, com ênfase no grotesco - Santos, Nelma Aronia (2013)
The purpose of this study is to analyze the processes of the media discourse present in the works of Rubem Fonseca. Among these processes, emphasis will be placed on the aesthetics of the grotesque and the spectacular, present both in his printed works and in the language used in its inner workings. The text corpus researched here covers the following sample of short stories by Fonseca: Livro de ocorrências, Corações solitários, Relato de ocorrência, Dia dos namorados, Duzentos e vinte e cinco gramas, Nau Catrineta and A arte de andar nas ruas do Rio de Janeiro. This text corpus was published between 1963 and 1992. It was selected due to the fact that its production provides a kind of narrative of the consolidation of mass communications media in our country. The main theoretical references on which our research is based include Mikhail Bakhtin, Wolfgang Kayser and Muniz Sodré, notable scholars of the grotesque; Guy Debord, a scholar of the society of the spectacle; Patrick Charaudeau, who describes and analyzes media discourse and is staging and expression strategies; Rildo Cosson, a scholar of hybrid texts, above all those that involve Brazilian journalism; David le Breton, who studies contemproary culture from the perspective of the body; and Zygmunt Bauman, for insight into human coexistence in the urban space. Our methodological procedure consists of allusive bibliographical research on the state of the art in studies and Brazilian media. The primary result is intended to be an observation of the potential for exchange between the spheres of literature and more popular media forms. We also intend to contribute to research that tries to comprehend the processes of literary creation from an inter-semiotic perspective